PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KREATIVITAS DAN PRESTASI BELAJAR - Febriansyah Febriansyah (UNIB Press, 2020)
The purpose of this study is to use Discovery Learning methods to improve students' creativity and achievement. This research has been carried out with classroom action research methods in SD Negeri 3 Merapi Barat This research was conducted in three cycles to find out that the application of Discovery Learning increases the creativity and achievement of students from the first cycle to the third cycle. This research proves that the application of the Discovery Learning learning model not only enhances student learning creativity but also increases the understanding of the material and this has animpact on increasing student learning achievement. PTK taking techniques by means of observation and tests. third. However, the control class was tested using conventional teaching methods with each class holding pretest and posttest. Then, it was continued with a significant analysis using t-test. Conventional if to improve creativity and student achievement in social